2016
DOI: 10.1136/bjsports-2015-094792
|View full text |Cite
|
Sign up to set email alerts
|

Are there three main subgroups within the patellofemoral pain population? A detailed characterisation study of 127 patients to help develop targeted intervention (TIPPs)

Abstract: BackgroundCurrent multimodal approaches for the management of non-specific patellofemoral pain are not optimal, however, targeted intervention for subgroups could improve patient outcomes. This study explores whether subgrouping of non-specific patellofemoral pain patients, using a series of low cost simple clinical tests, is possible.MethodThe exclusivity and clinical importance of potential subgroups was assessed by applying à priori test thresholds (1 SD) from seven clinical tests in a sample of adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 39 publications
(44 reference statements)
6
86
0
3
Order By: Relevance
“…Whilst both used healthy subjects Katoh et al [15] did not report the participants as athletic and this could explain the higher scores in this study. However, in contrast, Selfe et al [2] reported higher scores in a PFP patient population for the strong male subgroup (age >30; comparable to this study) which could support the theory that this subgroup of PFP patients have overload of the knee as a possible cause of pain.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Whilst both used healthy subjects Katoh et al [15] did not report the participants as athletic and this could explain the higher scores in this study. However, in contrast, Selfe et al [2] reported higher scores in a PFP patient population for the strong male subgroup (age >30; comparable to this study) which could support the theory that this subgroup of PFP patients have overload of the knee as a possible cause of pain.…”
Section: Discussionsupporting
confidence: 75%
“…To allow for dropouts a total of 20 were recruited into the study. Using a purposive sample of healthy male runners in the 18-39 age range ensured there was good ecological validity with the strong and physically active PFP subgroup as identified by Selfe et al [2]. All participants met this inclusion criteria with running at least once per week set as an acceptable frequency for physical activity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations